Reflections on Realization Paths of Curriculum Ideology and Politics in Senior High School English - 吴建欧 (Pacific International Journal, 2023)
Since the introduction of the concept of "Curriculum Ideology and Politics" in comprehensive education reform, senior high schools have actively embraced its implementation throughout the entire education process. However, due to the pressures of exam-oriented education, systematic integration into actual frontline teaching work has been challenging, with various factors hindering its development. These include difficulties in exploring ideological and political elements within textbooks, a lack of vitality in traditional teaching models, and outdated educational mechanisms. Considering that teachers play a crucial role as educational leaders, textbooks serve as the primary tools for teachers’ educational activities, and the education mechanism provides the institutional framework for teaching, these three interconnected components collectively shape the education and teaching process. Therefore, this study aims to explore the most suitable teaching mode for integrating foreign language ideological and political instruction into the curriculum through three paths: upgrading the teaching model, updating textbook content, and innovating the educational mechanism. To achieve this, the study will employ textbook analysis as a methodology and provide suggestions to textbook compilers on effectively integrating "Curriculum Ideology and Politics" into senior high school English teaching. These efforts aim to enhance the vitality of the English subject.